Informatics-Based Product-Service Systems for Point-of-Care Devices - Ajai, O.; Tiwari, Ashutosh; Alcock, Jeffrey R. (Cranfield University Press, 2009)
Informatics related to point-of-care devices denotes the ability to translate stand-alone biological data into meaningful information that can be interpreted to enable and support users in taking the most appropriate steps to aid in managing their health. This paper considers small point-of-care devices used outside healthcare environments, and presents glucometers as an example. The paper seeks to evaluate the current level of servitization of point-of-care testing devices and considers whether they are, or could form, the product-core of a product-service system. The type of product-service system, its informatics requirements, and the services such a system could provide are also considered.
Organised by: Cranfield University
Keywords: Informatics; Point-of-care testing; Medical Device; PSS; Product-Service System